Menumbuhkan Semangat Belajar Peserta Didik Melalui Quantum Learning: Perspektif Pendidikan Islam Kontemporer - Bayu Mujrimin; Maya Inayati Sari (Medan Resource Center, 2024)
Students’ learning motivation plays a crucial role in determining the success of the educational process, yet many learners in the contemporary era experience declining enthusiasm due to unsupportive environments and monotonous instructional practices. This study addresses how Quantum Learning can enhance students’ learning motivation and examines its compatibility with the values of contemporary Islamic education. The research employs a qualitative descriptive approach through library research by analyzing relevant literature on Quantum Learning and Islamic educational principles. The findings indicate that core elements of Quantum Learning, including a positive learning environment, emotional engagement, and holistic learning, align with Islamic concepts of internal motivation such as sincere intention (niyyah) and the pursuit of knowledge as an act of worship. The study argues that integrating Quantum Learning with Islamic educational values can foster an effective, engaging, and spiritually grounded learning system that supports both cognitive and affective development.